Diketopyrrolopyrrole (DPP) functionalized tetrathienothiophene (TTA) small molecules for organic thin film transistors and photovoltaic cells1. Issue 34 (14th September 2015) - Zhou, Nanjia; Vegiraju, Sureshraju; Yu, Xinge; Manley, Eric F.; Butler, Melanie R.; Leonardi, Matthew J.; Guo, Peijun; Zhao, Wei; Hu, Yan; Prabakaran, Kumaresan; Chang, Robert P. H.; Ratner, Mark A.; et al.
<x xml:space="preserve">Abstract</x> Diketopyrrolopyrrole (DPP) end capped tetrathienoacene (TTA) small molecules approaching the hole mobility 0.1 cm2 V−1 s−1 in OFET and efficiency >4% in OPV.